FAKTOR YANG MEMPENGARUHI PENINGKATAN KUALITAS PRODUK DAN HARGA SPARE PART MOBIL TERHADAP VOLUME PENJUALAN PADA PT. SINAR AGUNG PRASAKINDO - Shindu Hargo Dedali (Media Mahardhika, 2023)
At present, the number of products produced by spare part makers increases competition in the market. To maintain the continuity of its production, the Company must be able to attract as many consumers as possible so that sales volume can increase. Where the spare part business in Indonesia is a very potential and promising business. And this effort is needed by the Indonesian people. Because this is like a basic need. Because the average Indonesian people carry out their activities using their own vehicles, so spare parts must be replaced when they are past their expiration date. The efforts made by the Company to survive in the face of increasingly intense competition between companies, whether of the same type or not, can be carried out in various ways. One of them is by diversifying the products produced by producing new products to meet market tastes. The variables studied are Product Quality (X1), Price (X2) and Sales Volume (Y). The purpose of this research is that researchers want to know the increase in product quality and price on sales volume. Where it is useful as a  consideration for the company in making decisions about improving the quality and price  of products in the future so that the company can achieve its goals, so the researchers  conducted a study entitled "Factors Influencing Product Quality Improvement and Car Spare Part Prices Against Sales Volume at PT. Sinar Agung Prasakindo”.